Study guide to accompany Engineering mechanics. Volume 1 : Statics - Meriam, J. L. (James L.); Henderson, J. M. (New York ; Chichester : John Wiley and Sons, 1997)
Definitions and principles. Units. Problem formulation. Analysis techniques. Sums and components. Moments and couples. Resultants. Distributed forces. Center of mass and centroids...
Keywords: Engineering; Mechanics, Applied; Statics; Mechanics, Applied -- Problems, exercises, etc; Statics -- Problems, exercises, etc